The Role of Information Technology in Administrative Control: Analytical Study of the Babylon University's Community Views - JassimAbd AL-Razaq, Fryal; Saad A. AL-Murieb, Safa (International Journal of Engineering and Technology, 2018)
Due to the main role of information technology in many fields of life such as in administrative control  and the increasing occurred, the interest with this subject increased, this is occurred because a lot of processes are running by the organizations via the usage of information technology. So the problem of current research is (Is there a use of information technology in administrative  control, is there a role for IT in administrative control of the unit under study, and what is the most frequently used information technology field in the administrative  control) and adopted Find on two assumptions are the link to the role of the hypothesis of IT in administrative  control of the unit surveyed, The premise of the effect, and the goal of research is to identify the role of information technology in administrative  control, and identify the concepts of the role of information technology and administrative  control of the unit under study, has identified conduct research and Babylon university, as the total members of the research community 87 individuals were, in order ,the researchers use, analytical study, a meta search in the collection of information using the questionnaire methods, and use statistical means the arithmetic mean, standard deviation, and correlation coefficient for the completion of the requirements of the search.The research found a set of conclusions was the most important, there is the role of IT in administrative  control of the unit researched process, in terms of the use of information technology in administrative  control, and that the most widely used field of information technology in administrative  control is the financial and administrative field by virtue of the nature of their work.